2019
DOI: 10.1186/s13104-019-4267-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors associated with HIV/AIDS patients dropout from antiretroviral therapy at Mettu Karl Hospital, southwest Ethiopia

Abstract: Objective The aim of this study was to determine the major risk factors of antiretroviral therapy dropout. The retrospective cohort research design was applied. 1512 HIV patients were included from Mettu Karl Hospital in Illubabor Zone, southwest part of Ethiopia from September 2005 to January 2018. Kaplan–Meier comparison and log-logistic regression accelerated failure time model were used. Results From the log-logistic regression result, the risk of dropout for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Five original papers stated that marital status was associated with patient retention in clinical care. Of which three articles reported that married people were less likely to be lost to follow up [8,30,51] and the probability of dropout for patients with separated marital status was about 16.82% higher than those patients with marital status divorced [41]. Another article [44] reported as single marital status as an independent predictor of death.…”
Section: Factors Related To Patient Retention and Attrition Socio-demmentioning
confidence: 99%
See 2 more Smart Citations
“…Five original papers stated that marital status was associated with patient retention in clinical care. Of which three articles reported that married people were less likely to be lost to follow up [8,30,51] and the probability of dropout for patients with separated marital status was about 16.82% higher than those patients with marital status divorced [41]. Another article [44] reported as single marital status as an independent predictor of death.…”
Section: Factors Related To Patient Retention and Attrition Socio-demmentioning
confidence: 99%
“…Similarly, eight papers [17,22,23,28,30,36,49,54] reported that young age was an important predictor of loss to follow up but this was not statistically significant in the pooled analysis (OR, 0.88, 95% CI, 0.27-2.89). Four papers reported that educational status had an influence on retention in care [10,30,41,54]. All except one [41] primary articles has reported that people with no or primary education were more likely to experience loss to follow up compared to those with secondary and above educational level.…”
Section: Factors Related To Patient Retention and Attrition Socio-demmentioning
confidence: 99%
See 1 more Smart Citation
“…That means, Patient's baseline CD4+ count significantly impact on his or her survival attending follow-up time. This study was agreed to a study by [10] in Ethiopia.…”
Section: Discussionmentioning
confidence: 95%
“…Based on WHO report, out of the registered HIV patient's the measurement of achievement was only 23%. ART lost from follow-up negatively affects the improvement of an immunological advantage and increases HIV/AIDS related mortality [10]. Lost follow-up of ART will be the reason for drug toxicity, treatment poor adherence and medication resistance this results to mortality [11].…”
Section: Introductionmentioning
confidence: 99%